A case report on CREST syndrome with acrodermatitis - S. L., Adithya; D. P., Anfi; Dharan, Shaiju S.; Dharman, Dhanya (International Journal of Contemporary Pediatrics, 2024)
Acrodermatitis enteropathica (AE) is an autosomal recessive disorder, which is characterized by mutation affecting intestinal zinc absorption, subsequently leading to hypozincemia. In 20% of the cases, occurs the triad comprising dermatitis, alopecia and intractable diarrhoea as its diagnostic hallmark. The major manifestations include dermatitis, diarrhoea, alopecia, mood changes, anorexia, neurological disturbances, growth retardation, weight loss and recurrent infections. It is caused by mutations in the gene that encodes a membrane protein that binds zinc. Zinc is an essential coenzyme in metal enzymes (like ALP), which is important structural component of gene regulatory proteins and gene expression. Calcinosis, Raynaud phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasia (CREST) syndrome is a variant systemic sclerosis characterized by the presence of calcinosis, Raynaud’s phenomenon, oesophageal motility abnormalities, sclerodactyly and telangiectasia antinuclear antibodies recognizing chromosomal centromere proteins are characteristic of CREST syndrome and are present in more than 50% cases. Circulating antibodies against anti-nucleolar antigens are present in most patients with systemic scleroderma. Alterations of the blood vessels and induction of fibroblasts by potent mediators plays an important role in the early phase of scleroderma. Here, we present a case of 12-year-old girl child with insidious onset gradually progressive symptoms of dryness in both lower limbs, bluish discoloration of the fingers on exposure to cold, skin tightening over the face and hands, whitish pigmentation over the scalp and neck, whitish nodules progressing to ulceration over the posterior aspects of both elbows and difficulty in eating- both solids and liquids for 1-year duration.